The transition from winter to spring has an impact on the airway metabolome profile of asthmatic horses - Julia Drespling; Steffen Heelemann; Selina Strathmeyer; Heike Kühn; Bianca Schwarz; Lars Mundhenk (PLoS ONE, 2026)
Equine asthma is a chronic, non-infectious inflammatory disease of the lower airways in horses, classified as mild to moderate (MEA) or severe (SEA). Its pathogenesis is not fully understood and is influenced by environmental and seasonal factors. In this cross-sectional study, seasonal effects on the bronchoalveolar lavage fluid (BALF) metabolome were investigated in asthmatic and non-asthmatic horses. The metabolome of 230 BALF samples from horses across different seasons, classified as cytologically unremarkable (CUA), MEA, or SEA, was analyzed using proton nuclear magnetic resonance spectroscopy (1H-NMR). Principal component analysis was performed for each season, and metabolite profiles were statistically compared between seasons within each group. Altered metabolites were subjected to pathway enrichment analysis using the FELLA R package. Asthmatic horses showed significant seasonal changes in metabolite concentrations between warm and cold seasons, whereas only trends were observed in CUA horses. Pathway analysis indicated enrichment of cholesterol metabolism across all groups. The mTOR signaling pathway was only enriched in SEA horses. Several metabolites—including valine, taurine and carnitine —were altered during the transition from winter to spring in asthmatic horses. These findings indicate that the winter to spring transition significantly modulates the airway metabolome in asthmatic horses, particularly in SEA-affected animals.